Does corruption affects business innovation? Insights from emerging countries - Pirtea, Marilen Gabriel; Sipos, Gabriela Lucia; Ionescu, Alin (Journal of Business Economics and Management, 2019)
There are very different outcomes in the literature regarding the influences of corruption on business innovation and also arguments for both “sanding the wheels” and “greasing the wheels” approaches. The main goal pursued in this paper is to broaden the understanding of the corruption influence on business innovation, considering seven representative dimensions of corruption at governmental structures and institutions’ level and also four relevant dimensions of business innovation, less approached so far. The originality and relevance of this paper are based on that these seven different dimensions of corruption are targeting three characteristic features of it, as bribery's prevalence, the bribery's spread and the companies’ propensity to offer gifts for overcoming the bureaucratic pressures. Moreover, the four different new dimensions of business innovation are targeting the company’s propensity for innovating and strengthening its image and the way of connecting with business partners in a changing business environment. Considering an extensive data set for 110 emergent countries from four continents for the period between 2002 and 2014 and using the generalized linear model framework, this research study is emphasizing that corruption at governmental structures and institutional level has a significant negative impact on business innovation, adversely affecting innovation perspectives.